Comparative Functional Morphology of Skulls among Japanese Breeds of Domestic Fowls - Kudo, Kohei (J Poult Sci, 2016)
The skull of six Japanese fowl breeds, namely, Chabo, Oh-Shamo, Onagadori, Shokoku, Tosajidori, and Totenko, were morphologically compared in this study. The morphological differences in the skull size and shape among the breeds were as follows. 1) Oh-Shamo possessed a wide bill, thick bill tip, small orbits and wide mandibular joint. The characteristics of the bill and mandible were interpreted as functional characteristics to endure the shock of pecking. We suggest that the small orbits and a wide frontal bone help in protection from pecking in games. 2) Chabo possessed a small skull. In terms of shape, this breed possessed relatively large orbits, a wide and high skull and a short bill. The wide and high skull and the short bill formed a circular-shaped face. We propose that these characteristics have led to its characterisation as ornament-type fowl. 3) Totenko, Shokoku, Onagadori and Oh-Shamo possess a long mandible. The long mandible led to an increase in the volume of the oral cavity. The wide resonance space is responsible for the low-frequency voice. The low-frequency crowing of Totenko, Shokoku, Oh-Shamo and Onagadori is a result of the enlarged resonance space created by the long mandible. The orbits of Totenko and Onagadori were larger than those of Shokoku and Oh-Shamo. We suggest that Shokoku possessed the small orbits as a fighting cock. Since Onagadori and Totenko had been bred as ornament-type fowl, they possessed larger orbits.